The Effect of Acupressure Therapy on Nausea and Vomiting in Children with Acute Lymphoblastic Leukemia (ALL) Undergoing Chemotherapy - Velga Yazia; Ulfa Suryani (Indonesian Journal of Global Health Research, 2025)
The most common cancer in children is Acute Lymphoblastic Leukemia (ALL) with 14,979 cases in Indonesia. One of the cancer treatments is chemotherapy, which uses chemicals and has physiological side effects. One of the most common physiological side effects is nausea and vomiting, which is experienced by around 75% of patients. As a result, children experience fluid and electrolyte imbalances which negatively impact patient compliance in undergoing chemotherapy programs and are worried that patients will choose not to continue and stop their chemotherapy cycles due to discomfort caused by the side effects. Management of nausea and vomiting can be done with non-pharmacological therapy. One therapy that can be done is acupressure therapy at points P6 and St36, which is believed to improve energy flow in the stomach, thereby stimulating the release of beta endorphins in the pituitary gland, which can inhibit nausea and vomiting impulses in the vomiting center. The aim of this study was to determine the effect of acupressure therapy on nausea and vomiting in children with Acute Lymphoblastic Leukemia (ALL) undergoing chemotherapy at Dr. M. Djamil Padang General Hospital. Research methodology: using Quasi-Experimental with pre-experimental design with One-Group Pre-posttest design approach. The research sample was ALL pediatric patients undergoing chemotherapy, aged 6-18 years, experiencing nausea and vomiting and has been measured with the PeNAT instrument with results of 3 and 4, patients who were not given anti-emetic therapy. The sampling technique was carried out using purposive sampling technique. The population of this study was children with Acute Lymphoblastic Leukemia (ALL) aged 6-18 years who underwent chemotherapy at Dr. M. Djamil Padang Regional Hospital with a sample size of 15 people with the sample criteria being willing to be respondents, ALL child patients undergoing chemotherapy aged 6-18 years, who experienced nausea and vomiting. The study will be conducted within one year. Data analysis techniques were carried out univariately and bivariately with computerization. The results of the study showed that the average score of nausea and vomiting in children before the intervention was 3.467 and after the intervention was 2.133, with a mean difference of 1.334. The results of the statistical test using the Wilcoxon T-Test obtained a p-value = 0.000 ≤ 0.05, so it can be interpreted that there is an effect of acupressure therapy on nausea and vomiting in children with Acute Lymphoblastic Leukemia (ALL) undergoing chemotherapy at Dr. M Djamil Padang Hospital. The results of this study have shown that acupressure can significantly reduce nausea and vomiting scores in respondents who experience nausea and vomiting due to chemotherapy.